ORAL CONTRACEPTIVE USE AND BREAST CANCER RISK: A COMPREHENSIVE ANALYSIS IN THE PAKISTANI POPULATION - Dr Iqra Heer Bhatti; Dr. Amna Mughal; Dr Saira Bhatti; Dr Aisha Hasan Brohi; Dr. Sarah Zahid; Dr Uzma Hameed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Among the most common illnesses affecting women globally is breast cancer, which is still a major global health concern. This research thoroughly investigates the link between oral contraceptive use and breast cancer risk in the Pakistani population, aiming to clarify the correlation and provide insights for clinical practice and public health initiatives. Methodology: A one-year case-control study at Dr. Ruth K. M. Pfau, Civil Hospital Karachi examined the link between oral contraceptive use and breast cancer risk in Pakistani women. Including 20 cases and 20 controls, the study aimed for 80% power and 95% confidence, assuming an odds ratio of 1.5. Women aged 18-65 were surveyed, and logistic regression adjusted for confounders was used for analysis with SPSS. Results: Using a contraceptive pill for a mean of 4.5 years for diagnoses and 3.8 years for controls was linked to increased likelihood of developing cancers of the breast (OR: 1.45, 95% CI: 1.05–2.00). The kind of contraception used had no discernible effect on the incidence of breast cancer (OR: 1.25, 95% CI: 0.85–1.84), although BMI and family history had. Breast cancer risk was unaffected by age, age at menarche, age during the initial complete pregnancy, or menopause. Conclusion: The findings indicated a strong correlation with the risk of cancer of the breast and the usage of oral contraceptives. More women with cancer of their breasts than those without it reported using oral contraceptives. This study emphasizes the significance of more research and careful evaluation of contraceptive habits in breast cancer prevention measures for the Pakistani community.